Simple spectrophotometric methods for the simultaneous determination of antipyrine and benzocaine - Hanan A. Merey (Faculty of Pharmacy, Cairo University, 2016)
Antipyrine and benzocaine are formulated together for the treatment of ear inflammation and to relieve pain. Four spectrophotometric methods were developed for the simultaneous determination of antipyrine (AN) and benzocaine (BE) in their combined dosage form. Method A depends on applying dual wavelength method where antipyrine was determined by measuring the absorbance at 254.1 and 309.1 nm (corresponding to zero difference of benzocaine), while the absorbance difference at 230.1 and 263.5 nm (corresponding to zero difference of antipyrine) was selected for benzocaine determination in the laboratory prepared spectrum. Method B depends on measuring the peak amplitude of first derivative at 305 nm for calculating benzocaine concentration then the total concentration of both drugs was determined using isoabsorptive point at 257.4 nm (antipyrine concentration was then calculated by subtraction). Method C is based on measuring the peak difference of the ratio spectra at Δp (239.1-285 nm) and Δp (301.4-250 nm) for the determination of antipyrine and benzocaine, respectively. Method D depends on measuring peak to peak amplitude of the first derivative of ratio spectra at (234.5 + 244.2 nm) and peak amplitude at 295.5 nm for the determination of antipyrine and benzocaine, respectively. The proposed methods were validated and applied for the analysis of antipyrine and benzocaine in their laboratory prepared mixtures and pharmaceutical formulation. Statistical comparison between the results of the proposed methods and those of the reported methods showed no significant difference.